206k views
2 votes
What are the beginning steps of solving this?

2x + √(x + 1) = 8

1 Answer

5 votes

Isolate the radical term, then square both sides:


2x+√(x+1)=8


√(x+1)=8-2x

Note that
√(x+1) is non-negative and requires that
x\ge-1 in order to be defined, while
8-2x<0 when
x>4. This means we can only find real solutions in the range
-1\le x\le4.


(√(x+1))^2=(8-2x)^2


x+1=(8-2x)^2

Now just expand the RHS and simplify as much as possible:


x+1=64-32x+4x^2


4x^2-33x+63=0


(x-3)(4x-21)=0


\implies x=3,x=\frac{21}4

Now,
\frac{21}4=5.25, which is larger than 4, so we omit that solution. Then
x=3 is the only solution.

User DeltaTango
by
5.1k points